Sublingual epidermoid cyst in a neonate - Oginni, Fadekemi Olufunmilayo (Medknow Publications & Media Pvt Ltd, 2014)
Epidermoid cysts (EC) in the head and neck region could be considered a rare condition representing only 6.9% of all ECs occurring in the body. They occur rarely in children and neonates. We present a case of sublingual EC in a Nigerian neonate.